2003
DOI: 10.1084/jem.20031074
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Primary Mediastinal B Cell Lymphoma Identifies a Clinically Favorable Subgroup of Diffuse Large B Cell Lymphoma Related to Hodgkin Lymphoma

Abstract: Using current diagnostic criteria, primary mediastinal B cell lymphoma (PMBL) cannot be distinguished from other types of diffuse large B cell lymphoma (DLBCL) reliably. We used gene expression profiling to develop a more precise molecular diagnosis of PMBL. PMBL patients were considerably younger than other DLBCL patients, and their lymphomas frequently involved other thoracic structures but not extrathoracic sites typical of other DLBCLs. PMBL patients had a relatively favorable clinical outcome, with a 5-yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
801
0
21

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 986 publications
(845 citation statements)
references
References 34 publications
23
801
0
21
Order By: Relevance
“…13,14 Although additional subgroups within the germinal center diffuse large B-cell lymphomas based on the presence or absence of t(14;18)(q32;q21) have been defined, these did not predict survival. 15 Recently, an alternate approach, based on clustering of whole genome arrays has identified three new groups among diffuse large Bcell lymphomas: 'oxidative phosphorylation', 'B-cell receptor/proliferation', and 'host response', but these results were not associated with prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…13,14 Although additional subgroups within the germinal center diffuse large B-cell lymphomas based on the presence or absence of t(14;18)(q32;q21) have been defined, these did not predict survival. 15 Recently, an alternate approach, based on clustering of whole genome arrays has identified three new groups among diffuse large Bcell lymphomas: 'oxidative phosphorylation', 'B-cell receptor/proliferation', and 'host response', but these results were not associated with prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…Despite clear differences in age distribution, sex predominance, lymphoma spread, histology, and immunophenotype of the neoplastic cells between PMBL and cHL, there is a growing list of common characteristic hallmarks like mediastinal (thymic) origin, loss of MHC class I presentation, lack of immunoglobulin expression despite successfully rearranged IgH genes, lack and/or functional Oct2 deficiency, and frequent gains of 2p13-p16 and 9p24 involving REL and JAK2, respectively (Joos et al, 1996Barth et al, 2003;Savage et al, 2003;Ritz et al, 2005). Furthermore, two extensive studies on gene expression profiling revealed substantial similarities between PMBL and cHL cell lines in terms of commonly up-or downregulated genes (Rosenwald et al, 2003;Savage et al, 2003).…”
mentioning
confidence: 99%
“…24 Although four subtypes of diffuse large B-cell lymphoma were classified by cDNA microarray, the unclassified group was found to be heterogeneous and behaved in a manner similar to the activated B-cell group and the primary mediastinal group was found to characteristically develop from the mediastinum and was associated with a favorable prognosis. 13,14 Therefore, we classified diffuse large B-cell lymphoma cases into two groups: germinal center B-cell or nongerminal center B-cell group. The tissue microarray classification predicts survival similar to the cDNA microarray analysis.…”
Section: Interpretation and Hierarchical Cluster Analysis Of Tissue Mmentioning
confidence: 99%
“…11 Recent cDNA microarray studies have shown that diffuse large B-cell lymphoma can be divided into four distinct subgroups including: germinal center B-cell-like, activated B-cell-like, primary mediastinal, and unclassified gene expression profiles. [12][13][14][15] The activated B-cell and unclassified groups have a significantly inferior clinical outcome compared to the germinal center B-cell and primary mediastinal groups. The unclassified group is heterogeneous and not well defined, but has a poor outcome similar to that of the activated B-cell group.…”
mentioning
confidence: 99%
See 1 more Smart Citation